Four Layer Cylindrical Model of Mucus Transport in the Lung: Effect of Prolonged Cough (Bangladesh Journal of Medical Science, 2019)
Background: In this paper, a four layer model of the simultaneous and coaxial flow of moist air, mucus, mixture of mucin and periciliary liquid and serous fluid (assumed to be incompressible and Newtonian fluids) in a circular tube under time dependent pressure gradient representing prolonged cough is analyzed to study the mucus transport in an airway in the presence of prolonged cough. It is assumed that air and mucus flow under quasi steady state turbulent conditions while the mixture of mucin and periciliary liquid and serous layer surrounding mixture layer flows under unsteady laminar condition in presence of immotile cilia carpet.Result: It is shown that the mucus transport increases as the viscosity of serous fluid decreases. Also the mixture and serous fluid flow rates increase as the viscosity of serous fluid decreases. It is also observed that the effect of resistance to flow by serous fluid in the cilia bed is to decrease flow rates. The flow rates of mucus and mixture of mucin and periciliary fluid increase as the viscosity of mixture decreases also air and mixture of mucus and periciliary fluid flow rates increase as the thickness of mixture increases.Conclusion: As the thickness of mucus increases its flow rate increases on the other hand the mixture flow rate, mucus and serous fluid flow rate decreases with the increase of the mixture thickness.Bangladesh Journal of Medical Science Vol.19(1) 2020 p.53-63